2011
DOI: 10.1007/s00425-011-1472-2
|View full text |Cite
|
Sign up to set email alerts
|

Root starch accumulation in response to arbuscular mycorrhizal colonization differs among Lotus japonicus starch mutants

Abstract: Arbuscular mycorrhizal (AM) fungi are obligate symbionts dependent for completion of their life cycle on plant carbohydrates, which they trade for mineral nutrients. Plant colonization by AM fungi is therefore expected to induce profound changes in plant carbon metabolism. We have previously observed that on one hand starch accumulation increases in responses to pre-symbiotic fungal signals and on the other hand, it decreases in mycorrhizal Lotus japonicus roots (Gutjahr et al. in New Phytol 183:53-61, 2009). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Disappearance of starch in infected root cells was thought to be linked with sugar supply to AM fungi (Kinden and Brown, 1975;Smith and Gianinazzipearson, 1988). However, Lotus japonicus mutants impaired either in starch degradation or synthesis showed normal AM colonization, indicating that defects in starch metabolism do not affect AM development (Gutjahr et al, 2009(Gutjahr et al, , 2011. Early studies using 14 C labeled substrates suggested that hexoses were good candidates for transfer from plant to AM fungi Harley, 1965a, 1965b;Smith et al, 1969;Ho and Trappe, 1973;Solaiman and Saito, 1997).…”
Section: Sugar Transfer From Host Plants To Am Fungimentioning
confidence: 99%
“…Disappearance of starch in infected root cells was thought to be linked with sugar supply to AM fungi (Kinden and Brown, 1975;Smith and Gianinazzipearson, 1988). However, Lotus japonicus mutants impaired either in starch degradation or synthesis showed normal AM colonization, indicating that defects in starch metabolism do not affect AM development (Gutjahr et al, 2009(Gutjahr et al, , 2011. Early studies using 14 C labeled substrates suggested that hexoses were good candidates for transfer from plant to AM fungi Harley, 1965a, 1965b;Smith et al, 1969;Ho and Trappe, 1973;Solaiman and Saito, 1997).…”
Section: Sugar Transfer From Host Plants To Am Fungimentioning
confidence: 99%
“…S7). One possible function of starch is that it acts as a second source of energy for AMS (Gutjahr et al 2011). Following the fates of N-containing substances in addi-tion to amino acids, nitrate levels and total protein concentration were analysed (Supporting Information Fig.…”
Section: Mycorrhiza-induced Biomass Production Is Attended By a Shiftmentioning
confidence: 99%
“…Here, we show that high levels of sucrose (up to 1% of dry weight) accumulated in all stages of G. elata tubers (Figure 1), similar to autotrophic tuber plants such as potato (Schwimmer, Bevenue, Weston, & Potter, 1954), indicating that sucrose may be the predominant form of carbohydrate transported into G. elata at the symbiotic interface. A similar sucrose flow functions in the heterotrophic relationship between autotrophic and parasitic plant species (Péron et al, 2017), and at the symbiotic interface between plants and AM fungi (Boldt et al, 2011; Doidy, van Tuinen, et al, 2012; Garcia et al, 2016; Gutjahr et al, 2011). Some of this sucrose is likely used for starch biosynthesis given the numerous starch grains observed in infected cortical cells and neighbouring large cells (Figure 2b) (Yeh et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…Due to the lack of fatty acid synthesis in AM, lipids transferred from plants could be the carbon source (Keymer & Gutjahr, 2018). Nevertheless, soluble sugars, such as sucrose or hexoses, are probably the major form of carbon flow (Garcia, Doidy, Zimmermann, Wipf, & Courty, 2016; Gutjahr, Novero, Welham, Wang, & Bonfante, 2011). Sugar transporters have been identified that localize on adjacent plant and fungal cells and these may fine‐tune sugar exchange ensuring benefits for both partners in this symbiotic relationship (Doidy et al, 2012; Hennion et al, 2019).…”
Section: Introductionmentioning
confidence: 99%